John Chrysostom on Manichaeism - De Wet, Chris L. (HTS teologiese studies, 2019)
This article examines John Chrysostom’s (ca. 349–407 CE) statements about Manichaeism. The study enquires regarding the extent of Chrysostom’s knowledge of Manichaean beliefs and practices, and whether he possibly had contact with Manichaeans. The study is not so much interested in determining how accurately or inaccurately Chrysostom understands and characterises Manichaeism, although at some points the analysis does venture into some of these issues. In the first instance, Chrysostom’s views about Manichaean theology and, especially, Christology are delineated. Proceeding from the negative evaluation of the material cosmos in Manichaeism, the study then looks at Chrysostom’s critique of Manichaean views of the body, especially as it relates to freedom of choice. Chrysostom’s accusations of Manichaean practices, namely, starving as salvation and the accusation of castration, are also examined. Finally, Chrysostom’s response to the Manichaean rejection of a corporeal resurrection is analysed, after which some conclusions are drawn.